2023
DOI: 10.3390/ijerph20020955
|View full text |Cite
|
Sign up to set email alerts
|

(Dis)Agreement with Dysthanasia, Religiosity and Spiritual Experience as Factors Related to Nurses’ Workload during End-of-Life Care

Abstract: This study intended to investigate whether the workload of nurses in the course of providing end-of-life care correlated with their religiousness, spiritual experience and level of agreement with dysthanasia procedures. The respondents included 279 nurses from four Croatian hospitals. A structured and validated instrument was applied. Almost 90% of respondents are religious, and almost 45% of them have daily spiritual experiences. Respondents, especially those with high levels of religiousness and spiritual ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…However, the study also revealed that RNs' cultural, religious, educational and/or ethnic backgrounds may influence end‐of‐life nursing practices (Rittle, 2015 ). This is consistent with existing literature that highlights how cultural norms and education play a crucial role in shaping RNs' beliefs about death and dying and influence the provision of care (Binda et al, 2021 ; Juranić et al, 2023 ). These findings highlight the need to examine these factors to develop recommendations for improving end‐of‐life care practices in Saudi Arabia and internationally.…”
Section: Discussionsupporting
confidence: 90%
“…However, the study also revealed that RNs' cultural, religious, educational and/or ethnic backgrounds may influence end‐of‐life nursing practices (Rittle, 2015 ). This is consistent with existing literature that highlights how cultural norms and education play a crucial role in shaping RNs' beliefs about death and dying and influence the provision of care (Binda et al, 2021 ; Juranić et al, 2023 ). These findings highlight the need to examine these factors to develop recommendations for improving end‐of‐life care practices in Saudi Arabia and internationally.…”
Section: Discussionsupporting
confidence: 90%
“…The rapid development of modern technology in all scientific fields, including clinical medicine, has intensified efforts to prolong the life of healthy people, as well as those suffering from serious or terminal illness [13]. Dysthanasia (from Greek: dys, difficult; and thanatos-death; meaning "to die with difficulty") is a relatively new concept developed within bioethics, and refers to the application of medical procedures designed to maintain life at all costs, even when the disease is not curable, and the medical procedures often prolong the patient's pain and suffering.…”
Section: Dysthanasiamentioning
confidence: 99%
“…Consequently, dysthanasia is more fre-quently studied and discussed in scientific and professional literature. In high-tech hospitals around the world, dysthanasia procedures are becoming commonplace and are practiced when doctors, nurses, and other healthcare providers are pressured by patients' families to do everything in their power to keep patients alive [13].…”
Section: Dysthanasiamentioning
confidence: 99%